Indium Selenide/Indium Tin Oxide Hybrid Films for Solution‐Processed Photoelectrochemical‐Type Photodetectors in Aqueous Media. Issue 1 (20th October 2022) - Bianca, Gabriele; Zappia, Marilena Isabella; Bellani, Sebastiano; Ghini, Michele; Curreli, Nicola; Buha, Joka; Galli, Valerio; Prato, Mirko; Soll, Aljoscha; Sofer, Zdeněk; Lanzani, Guglielmo; Kriegel, Ilka; et al.
Abstract: 2D metal monochalcogenides have recently attracted interest for photoelectrochemical (PEC) applications in aqueous electrolytes. Their optical bandgap in the visible and near‐infrared spectral region is adequate for energy conversion and photodetection/sensing. Their large surface‐to‐volume ratio guarantees that the charge carriers are photogenerated at the material/electrolyte interface, where redox reactions occur, minimizing recombination processes. However, solution‐processed photoelectrodes based on these materials exhibit energy conversion efficiencies that are far from the current state of the art expressed by established technologies. This work reports a systematic morphological, spectroscopic, and PEC characterization of solution‐processed films of photoactive InSe flakes for PEC‐type photodetectors. By optimizing the thickness and hybridizing InSe flakes with electrically conductive Sn:In2 O3 (ITO) nanocrystals, photoanodes with a significant photoanodic response in both acidic and alkaline media are designed, reaching responsivity up to 60.0 mA W −1 (external quantum efficiency = 16.4%) at +0.4 V versus RHE under visible illumination. In addition, a strategy based on the use of sacrificial agents (i.e., 2‐propanol and Na2 SO3 ) is proposed to improve the stability of the InSe and ITO/InSe photodetectors. Our data confirm the potential of 2D InSe for PEC energy conversion and sensing applications, remarking the challenges related to InSe stability during anodic operation. Abstract : Two‐dimensional indium selenide/indium tin oxide (InSe/ITO) hybrid films have been designed for the realization of solution‐processed photoelectrochemical‐type photodetectors in aqueous media, reaching responsivity up to 60 mA W −1 (external quantum efficiency = 16.4%) under visible illumination.